2021
DOI: 10.3390/jcm10051119
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adding Biological Factors to the Decision-Making Process for Spinal Metastasis of Non-Small Cell Lung Cancer

Abstract: Molecular target therapies have markedly improved the survival of non-small cell lung cancer (NSCLC) patients, especially those with epidermal growth factor receptor (EGFR) mutations. A positive EGFR mutation is even more critical when the chronicity of spinal metastasis is considered. However, most prognostic models that estimate the life expectancy of spinal metastasis patients do not include these biological factors. We retrospectively reviewed 85 consecutive NSCLC patients who underwent palliative surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…This finding is interesting because the mean Tokuhashi in included cohorts was 5.2 points, meaning that expected life expectancy was less than six months. It is consistent with a previous report that positive EGFR mutation provided longer postoperative survival for NSCLC patients undergoing palliative surgical treatment for spinal metastases (HR = 2.10, p = 0.002) [35]. Furthermore, Batista et al demonstrated that the median survival of patients treated with EGFR inhibitors was improved up to 18 months.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is interesting because the mean Tokuhashi in included cohorts was 5.2 points, meaning that expected life expectancy was less than six months. It is consistent with a previous report that positive EGFR mutation provided longer postoperative survival for NSCLC patients undergoing palliative surgical treatment for spinal metastases (HR = 2.10, p = 0.002) [35]. Furthermore, Batista et al demonstrated that the median survival of patients treated with EGFR inhibitors was improved up to 18 months.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study demonstrated that local control of a spinal metastasis of renal cell carcinoma also improved with MTT [ 9 ]. Among patients with renal cell carcinoma, the combination of MTT and surgery for a bone metastasis significantly improved overall survival [ 8 , 15 , 16 ]. Our study further supported the existing data suggesting that MTT conferred significantly longer survival on patients who received the therapy than on those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the introduction of molecularly targeted therapy (MTT) has dramatically improved patients' prognoses [5][6][7]. Additionally, there exists a report indicating that individuals afflicted with spinal metastasis may achieve a more favorable prognosis if they are candidates for MTT as a form of treatment [8]. Patients with a spinal metastasis of renal cell carcinoma treated with radiotherapy and MTT showed a higher local progression-free rate than patients who did not receive MTT [9], suggesting that MTT improves not only life expectancy but also local control of spinal metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of target mutations include epidermal growth factor receptor (EGFR) in nonsmall cell lung cancer, v-raf murine sarcoma viral oncogene homolog B1 in melanoma, and hormonal receptors in breast and prostate cancers. Recently, Kim et al [38] discovered that the addition of EGFR mutation positivity to the NESMS system improves its discrimination ability. Their results emphasize the importance of genetic profiles while establishing treatment strategies for spinal metastasis.…”
Section: Current Trends and Future Directionsmentioning
confidence: 99%